Hydrogen production using methane: Techno-economics of decarbonizing fuels and chemicals. (1st February 2018) - Parkinson, Brett; Tabatabaei, Mojgan; Upham, David C.; Ballinger, Benjamin; Greig, Chris; Smart, Simon; McFarland, Eric
Abstract: In the near-to-medium future, hydrogen production will continue to rely on reforming of widely available and relatively low-cost fossil resources. A techno-economic framework is described that compares the current best practice steam methane reforming (SMR) with potential pathways for low-CO2 hydrogen production; (i) Electrolysis coupled to sustainable renewable electricity sources; (ii) Reforming of hydrocarbons coupled with carbon capture and sequestration (CCS) and; (iii) Thermal dissociation of hydrocarbons into hydrogen and carbon (pyrolysis). For methane pyrolysis, a process based on a catalytic molten Ni-Bi alloy is described and used for comparative cost estimates. In the absence of a price on carbon, SMR has the lowest cost of hydrogen production. For low-CO2 hydrogen production, methane pyrolysis is significantly more economical than electrochemical-based processes using commercial renewable power sources. At a carbon price exceeding $21 t −1 CO2 equivalent, pyrolysis may represent the most cost-effective means of producing low-CO2 hydrogen and competes favorably to SMR with carbon capture and sequestration. The current cost disparity between renewable and fossil-based hydrogen production suggests that if hydrogen is to fulfil an expanding role in a low CO2 future, then large-scale production of hydrogen from methane pyrolysis is the most cost-effective means during the transition period while infrastructure and end-use applications are deployed. Graphical abstract: Highlights: A catalytic molten Ni-Bi alloy system design for a novel methane pyrolysis process is presented. A techno-economic framework for deep decarbonisation of hydrogen production is developed. Fugitive natural gas emissions on decarbonisation opportunities are assessed. Specific areas for economic improvement in molten metal pyrolysis systems are identified. Process economics are competitive with state-of-the-art hydrogen production with low carbon prices.